1962
DOI: 10.1071/bi9620732
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Groups in Wool and Extracted Wool Proteins

Abstract: SummaryN . acetyl groups have been shown to exist in wool and in proteins extracted from wool after reduction with mercaptoethanol followed by alkylation with iodoacetate or after oxidation with performic acid. The evidence suggests that these acetyl groups are located on N-terminal amino groups of peptide chains rather than on the E-amino groups of lysine.Acid hydrolysis with 12N sulphuric acid was found to be preferable to alkaline hydrolysis for the release of acetic acid from the N-acetyl groups, since alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1962
1962
1977
1977

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…More recently Brown et al (1961) have reported that 8M urea or exposure to pH 10·5 will disaggregate the protein complex procarboxypeptidase into three discrete protein subunits each approximately onethird in size of the procarboxypeptidase and possessing distinct biological activities. We have previously reported Thompson and O'Donnell 1962) that chromatography oflow-sulphur wool proteins on DEAE-cellulose in buffers containing 8M urea leads to resolution of components which show differences in amino acid compositions consistent with the presence of X-keratose in the more strongly bound fractions. Thus the more acidic fraction is richer in cysteic acid, proline, glycine, serine, and tyrosine and lower in lysine and alanine, characteristics of the composition of X-keratose.…”
Section: Disoussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently Brown et al (1961) have reported that 8M urea or exposure to pH 10·5 will disaggregate the protein complex procarboxypeptidase into three discrete protein subunits each approximately onethird in size of the procarboxypeptidase and possessing distinct biological activities. We have previously reported Thompson and O'Donnell 1962) that chromatography oflow-sulphur wool proteins on DEAE-cellulose in buffers containing 8M urea leads to resolution of components which show differences in amino acid compositions consistent with the presence of X-keratose in the more strongly bound fractions. Thus the more acidic fraction is richer in cysteic acid, proline, glycine, serine, and tyrosine and lower in lysine and alanine, characteristics of the composition of X-keratose.…”
Section: Disoussionmentioning
confidence: 99%
“…Horner (1954) has reported that hydrolysis of amide bonds in wool does not occur readily at pH 13·3 at 25°C. The simplest explanation for the increase in ninhydrin colour given by these proteins at pH values above approximately pH 10·5 is that there is breakage of peptide bonds although we cannot definitely exclude the possibility that there is a release of additional ninhydrin-reacting groups due to unfolding or disaggregation, or hydrolysis of N-acetyl residues (O'Donnell, Thompson, and Inglis 1962).…”
Section: (E) Effect Of High Ph On the Breakage Of Peptide Bondsmentioning
confidence: 99%
See 3 more Smart Citations